Influence of ultrasonic compaction conditions of the (Ba,Sr)TiO3 nanopowder on the pore distribution in sintered ceramics; Korus 2001; Vol. 2 - Khasanov O. L. Oleg Leonidovich; Hahn S. R.; Dvilis E. S. Edgar Sergeevich; Han M. S.; Lim S. S.; Sokolov V. M. Vitaly Mikhailovich; Milovanova T. V. (2001, 2001)
The pore distribution on the wafer surface of ferroelectric ceramics Ba0.6Sr0.3Ca0.1TiO3 was investigated. The samples with diameter of 38-40 mm were sintered from green compacts being compacted under ultrasound action with a power of 1-3 kW and by uniaxial static moulding. The pore distributions were determined inside of wafer surface regions located from central point toward edges using SEM data. The software ImageJ1.16 was used. The distribution regularities of small (less than 5 microns) and large pores depending on sample manufacture conditions were determined.